Sistem Pendukung Keputusan Pemilihan Teknisi Terbaik Menggunakan Metode Hibrid AHP-COPRAS Pada PT. Telkom Akses Regional 4 - Rejani, Haikal Fikri; Agus Prasetyo Utomo (STEKOM PRESS, 2023)
Someone who is referred to as a technician is a person who has expertise in a particular field of technology. Telkom Group is the only state-owned telecommunications company and the largest telecommunications and network service provider in Indonesia. Evaluation of technician performance is important to support the smooth running of the company. Selection of the best technician, will increase the motivation of the technician's performance. Some of the problems encountered were the absence of a technician performance appraisal process, the absence of an appropriate selection method, and the absence of a Decision Support System (DSS) that could make it easier to assess the selection of the best technician. Designing and building a decision support system using the AHP and COPRAS methods on technician assessments at PT. Telkom Access Regional 4 (Semarang) to increase the morale of the technicians and appreciate them. In this study, the AHP-COPRAS method was used to create a web-based DSS, in providing a more objective assessment every month, and creating several reports that convey effective issues, such as rating reports and technician performance appraisal reports according to these criteria.